Boliglokalisering og andelen af regionale togrejser på Sjælland og i Østjylland: Andelen af regionale togrejser i en mono‐ og polycentrisk byregionsstruktur – Baggrund, effekter og perspektiver - Møller, Thomas Hjorth; Harder, Henrik; Nielsen, Thomas Sick (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
This scientific paper will compare previous studies of residential location and travel in a number of Danish cities, with a new study of relationships between residential location and use of regional train in the two Danish metropolitan areas; the polycentric region in East Jutland and the monocentric region in Zealand. The state of the art knowledge of relationship between residential location and travel is based primary on studies in monocentric urban region. The influence of residential location on travel herein use of regional train in polycentric urban regions is lesser known. Therefore the results of the study give an imported insight of how, use of train is affected by different structures of urban regions.